2020
DOI: 10.4103/jfmpc.jfmpc_840_20
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in patients of chronic kidney disease undergoing haemodialysis: A study from western Rajasthan

Abstract: Background and Aims: Chronic kidney disease (CKD) is a long standing debilitating medical condition. CKD patients who are undergoing hemodialysis commonly experience depressive and anxiety symptoms because of various physical and psychosocial factors. The present study aimed to assess psychiatric morbidities i.e., depression and/or anxiety in patients with CKD undergoing hemodialysis. The objective of study was to evaluate depressive and anxiety disorders and their relation to socio-demographic fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
(8 reference statements)
8
10
0
Order By: Relevance
“…Previous studies have shown that gender, educational level [1], serum creatinine concentration [6], and duration of HD [7], are associated with depressive symptoms in patients receiving HD. The illiterate patients had more depressive symptoms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that gender, educational level [1], serum creatinine concentration [6], and duration of HD [7], are associated with depressive symptoms in patients receiving HD. The illiterate patients had more depressive symptoms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Participants (3 studies) from AFR [30,58,70]; 4,295 (14 studies) from EUR [31,33,34,36,39,43,56,61,66,68,75,78,80,82]; 3,962 (17 studies) from AMR [22,23,24,25,26,29,32,35,38,45,53,55,62,65,67,69,77]; 679 (7 studies) from EMR [40,49,51,60,64,74,81]; 846 (7 studies) from SEAR [28,47,50,59,71,73,79], and 69,660 (13 studies) from the WPR. [27,37,41,42,44,46,48,52,54,57,63,72,76] Figure 2 shows the geographical distribution of the continents of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical diagnostic criteria included those of the DSM (20 studies, 2,028 participants) [23,26,27,28,32,34,35,42,46,49,56,60,66,67,70,72,73,74,76,78] ICD (5 studies, 69,954 participants) [25,37,47,71,79] SCID (15 studies, 1,435 participants)[22,33,39,40,43,48,51,53,54,56,57,59,61,65,82], and MINI (21 studies, 6,274 participants). [24,29,30,31,36,38,41,44,45,50,52,55,58,62,64,68,69,75,77,80,81] The sample size of the component studies ranged from 20 [70] to 67,866 [37] patients, with the proportion of women ranging from 0% [25] to 68% [74].…”
Section: Resultsmentioning
confidence: 99%
“…Studies from Asia reported higher frequencies of depression in patients with ESRD in urban than in rural areas [24]. Low income [43], unemployment [2] and low education levels [29] are risk factors for depression of CKD or dialysis patients. However, in the reportings of prevalence of depression, adjustment of socioeconomic factors is usually not made.…”
Section: Related Risk Factorsmentioning
confidence: 99%
“…Family support can partially reduce patients’ psychological pressure and enhance physical QOL; appraisal support mediates the relationship between sleep disturbances and depressive symptoms [34]. However, family burdens related to a spouse [43] and number of children [29] are also risk factors for depression.…”
Section: Related Risk Factorsmentioning
confidence: 99%